Azadirachta indica Fruit Mucilage Aided Mucoadhesive Microspheres of Acyclovir for Drug Entrapment and Mucoadhesive Time Assets with Design-Expert Software - Babu, Gorantla Naresh; Menaka, M; Ahad, Hindustan Abdul (Indian Journal of Pharmaceutical Education and Research, 2025)
Introduction Mucoadhesive microspheres for drug delivery are retained in the stomach for an extended period for localized drug release and effect. Objectives This research aims to explore the mucoadhesive properties of Azadirachta indica fruit mucilage when incorporated into mucoadhesive microspheres, utilizing Acyclovir as a model drug. Materials and Methods Employing a Box Behnken design, 13 formulations of microspheres were developed, varying Azadirachta indica Mucilage (AIFM) levels, carbomer 934P and stirring speed. Design Expert software was used to assess the impact of these factors on entrapment efficacy and mucoadhesion time. Congeniality studies involved the examination of microspheres for Acyclovir content and discharge. Results Results indicated that Acyclovir entrapment increased with higher AIFM levels and mucoadhesion time was prolonged in formulations with elevated AIFM levels. The optimal stirring speed was determined to be 750 rpm. Conclusion The study concludes that Acyclovir demonstrates effective stomach-specific drug delivery through carbomer 934P, further enhanced by Azadirachta indica fruit mucilage, particularly at a stirring speed of 750 rpm in the formulation of mucoadhesive microspheres.
Keywords: Acyclovir; Azadirachta indica; Design; Delivery; Microspheres; Mucoadhesion